Dangerous arachnids—Fake news or reality?. (November 2017) - Hauke, Tobias J.; Herzig, Volker
Abstract: The public perception of spiders and scorpions is skewed towards the potential harm they can inflict in humans, despite recent scientific evidence that arachnid venom components might be useful as bioinsecticides or even human therapeutics. Nevertheless, arachnids are becoming more popular as pets in Europe, America and Asia, raising the question for regulatory agencies in these regions as to whether they need to take measurements to protect their citizens. In order to decide upon the necessary regulatory steps, they first need to determine which arachnids are actually dangerous to humans. This review therefore provides an overview of the current literature on verified bites and stings from spiders and scorpions with the aim of assessing their potential danger for human health. As a guideline, we also provide a list of those arachnid genera that we consider as potentially dangerous, which includes 10 spider and 11 scorpion genera. The arachnid genera classified as dangerous comprise less than a quarter of all extant scorpion species and only 0.5% of all spiders species, with the actual number most likely being much lower than that, as not all species in those genera might turn out to pose an actual threat for humans. In conclusion, we found that only a small percentage of scorpions and a minute percentage of all spiders can be considered as potentially dangerous to humans. While in some countries of origin the high incidence of envenomations by dangerous arachnids can result in a serious problem to the health system, we assessed the risk that the same species pose when kept as pets under controlled maintenance conditions as significantly lower. Graphical abstract: Highlights: The increasing popularity of pet arachnids urges some governments to take protective steps to prevent serious envenomations. A literature review was carried out to assess which arachnids can be classified as potentially dangerous. About 0.5% of all spider and 23% of all scorpion species were classified as potentially dangerous. Even envenomations from the most dangerous arachnids have a low percentage of serious or even fatal consequences. We conclude that the public threat from pet arachnid envenomations has been overrated.